Soft Robot Fingers using 3D Printing - Nazir, Anis Syazani; Ribuan, Mohamed Najib (Evolution in Electrical and Electronic Engineering, 2021)
Soft robot fingers are a new and undiscovered technology and the main objective is to design soft robot fingers using elastic and flexible material at the joint and tendon part.  It also develops soft robot fingers that can have the same function as human fingers using the actual size and are designed using SolidWorks. The construction and coding of soft robot fingers will be the focus on the bending behaviour of various flexure hinges. This product will fabricate using 3D printing using material such as Thermoplastic Polyurethane (TPU) for its joint and Polylactic Acid (PLA) for the stiff part. These soft robot fingers will be tested with bending testing and grasping testing. These soft robot fingers can produce good bending and similar to human fingers.